2021
DOI: 10.1111/jdi.13685
|View full text |Cite
|
Sign up to set email alerts
|

Association between visceral adiposity index and risk of prediabetes: A meta‐analysis of observational studies

Abstract: Background and Objective: Epidemiological studies suggested that the association between the visceral adiposity index (VAI) and the risk of prediabetes is inconsistent. Whether VAI is a useful predictor of prediabetes remains unclear. Up until April 2021, there had been no systematic review on this topic. In this meta-analysis, the available observational epidemiological evidence was synthesized to identify the association between VAI and prediabetes risk. Methods: PubMed, EMBASE, and Cochrane databases in any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The VAI is another reliable lipid index to estimate insulin resistance from visceral adiposity dysfunction [ 19 ]. A meta-analysis included ten observational studies involving 112,603 participants found that VAI may be related to a high risk of prediabetes [ 55 ]. A recent meta-analysis included nine cohort studies showed that each 1-unit increment of VAI was associated with 42% higher risk of T2DM [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VAI is another reliable lipid index to estimate insulin resistance from visceral adiposity dysfunction [ 19 ]. A meta-analysis included ten observational studies involving 112,603 participants found that VAI may be related to a high risk of prediabetes [ 55 ]. A recent meta-analysis included nine cohort studies showed that each 1-unit increment of VAI was associated with 42% higher risk of T2DM [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanisms for the relationship of these indicators with T2DM among hypertensive patients are unclear, several hypotheses were proposed. Increased visceral adipose is linked to an increased risk of insulin resistance and β-cell dysfunction [ 55 ]. As the markers of visceral adiposity, increased LAP, VAI, and enlarged WC could promote the accumulation of various inflammatory cytokines, which could accelerate the progression of insulin resistance and glucose intolerance and cause the development of diabetes directly [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that 4 of the final 30 studies reported HR and one reported RR in risk evaluation [ 27 ]. Since OR was a commonly used indicator in case-control studies in epidemiology [ 48 ], the reported RR/HR data was regarded as OR as an approximation [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prediabetes refers to the condition of impaired glucose regulation, with blood glucose levels above the normal range but lower than the standard range for diabetes. At present, prediabetes also refers to poor glucose tolerance and/or impaired fasting glucose ( 1 ). In this study, the effects of MBPs on prediabetic mice were studied.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired glucose tolerance is a typical symptom of prediabetes, in which individual blood glucose levels increase but do not meet the diagnostic criteria for diabetes, representing the intermediate state between normal glucose metabolism and diabetes ( 1 ). Prediabetes is often more common than diabetes; 10% of patients with prediabetes develop type II diabetes (T2DM) each year ( 1 ). It is estimated that by 2030, more than 470 million people worldwide will have prediabetes.…”
Section: Introductionmentioning
confidence: 99%